A positive ground state solution for a class of asymptotically periodic Schrödinger equations with critical exponent. (October 2016) - Liu, Jiu; Liao, Jia-Feng; Tang, Chun-Lei
Abstract: In the paper, by using a new condition, a class of asymptotically periodic Schrödinger equations with critical exponent are studied. Via the variational method, a positive ground state solution is obtained.